2013
DOI: 10.5483/bmbrep.2013.46.12.133
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of luteolin-7-O-glucoside-induced growth inhibition on human liver cancer cells: G2/M cell cycle arrest and caspase-independent apoptotic signaling pathways

Abstract: Luteolin-7-O-glucoside (LUT7G), a flavone subclass of flavonoids, has been found to increase anti-oxidant and anti-inflammatory activity, as well as cytotoxic effects. However, the mechanism of how LUT7G induces apoptosis and regulates cell cycles remains poorly understood. In this study, we examined the effects of LUT7G on the growth inhibition of tumors, cell cycle arrest, induction of ROS generation, and the involved signaling pathway in human hepatocarcinoma HepG2 cells. The proliferation of HepG2 cells wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…Many studies have shown that flavonoids may protect cardiomyocytes against I/R injury (Yuan et al, ; Zhang et al, ). Lut, a flavonoid compound extracted from honeysuckle, exhibits anti‐inflammatory, antiviral, and anticancer properties (Cao et al, ; Hwang, Lee, Kim, & Hwang, ; Jung, Jin, Min, Kim, & Choi, ; Tian et al, ) and has shown promising results in myocardial cells. A/R injury was used to model I/R injury in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that flavonoids may protect cardiomyocytes against I/R injury (Yuan et al, ; Zhang et al, ). Lut, a flavonoid compound extracted from honeysuckle, exhibits anti‐inflammatory, antiviral, and anticancer properties (Cao et al, ; Hwang, Lee, Kim, & Hwang, ; Jung, Jin, Min, Kim, & Choi, ; Tian et al, ) and has shown promising results in myocardial cells. A/R injury was used to model I/R injury in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of intracellular ROS levels 2 ,7 -dichlorofluorescein diacetate (DCF-DA) staining was used to determine intracellular ROS levels, we performed as described previously (Ahn et al, 2013;Hwang et al, 2013). After Raw 264.7 cells were treated with Tat-BLVRA protein, the cells were treated with LPS (1 g) for 30 min.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Previous studies indicate that luteolin suppress cancer cell growth through multiple mechanisms including promoting cancer cell apoptosis and cell cycle arrest, inhibiting cell proliferation and tumor growth, improving drug resistance, and mitigating invasiveness and metastasis of cancer cells (Cook, Liang, Besch-Williford, & Hyder, 2017;Wang et al, 2014). Specifically, it has been found that luteolin inhibited the tumor formation in vivo through its antioxidant and anti-inflammatory activity (Hwang, Lee, Kim, & Hwang, 2013). Furthermore, luteolin effectively blocked progestin-dependent angiogenesis and the stem cell-like phenotype in human breast cancer cells (Cook, 2018).…”
mentioning
confidence: 99%